2012
DOI: 10.1163/187847611x620946
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ground Contact and Visible Horizon on Perception of Distance and Size under Severely Degraded Vision

Abstract: For low vision navigation, misperceiving the locations of hazards can have serious consequences. Potential sources of such misperceptions are hazards that are not visually associated with the ground plane, thus, depriving the viewer of important perspective cues for egocentric distance. In Experiment 1, we assessed absolute distance and size judgments to targets on stands under degraded vision conditions. Normally sighted observers wore blur goggles that severely reduced acuity and contrast, and viewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…This outcome may be surprising, given the diminished level of acuity when targets are more eccentric. These data are in accord with work by Rand and colleagues (Rand et al., 2011, 2012) showing that floor-level targets can be localized reasonably well even when viewed through blurred goggles. The practical import of these findings is that angular declination is a source of information that is useful even for individuals with low vision.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This outcome may be surprising, given the diminished level of acuity when targets are more eccentric. These data are in accord with work by Rand and colleagues (Rand et al., 2011, 2012) showing that floor-level targets can be localized reasonably well even when viewed through blurred goggles. The practical import of these findings is that angular declination is a source of information that is useful even for individuals with low vision.…”
Section: Discussionsupporting
confidence: 91%
“…This outcome is empirically intriguing, to be sure, but it is also theoretically compelling in that it demonstrates that visual cues are not needed to make use of angular direction as a cue to distance. Theorists have suggested that the visible horizon is used as reference for making use of angular direction (Ozkan & Braunstein, 2010; Rand, Tarampi, Creem-Regehr, & Thompson, 2011, 2012), visual cues to eye level are generally thought beneficial, and a visual representation of the ground surface is important in existing theory (He et al, 2004; Wu et al, 2004). We show here that retinal and/or extraretinal sources of information about angular direction, coupled with the assumption that the object is on the ground, can support a well-constrained judgment of distance.…”
Section: Discussionmentioning
confidence: 99%
“…A cue for identifying a ramp was its elevation in the image Visibility of steps down is of particular concern and may be enhanced by contrast between riser and contiguous surface, and directional lighting Rand et al ( 2011 ) Blur (severe) logMAR = 1.60 (20/791) Distance perception to targets Visual horizon height (wall-floor boundary): actual or raised Distance: 3, 4.5, 6 m 1. When the “horizon” was raised, the angle of declination to the target increased, and viewers judged the distance to targets on the ground to be closer Create high contrast between wall and floor to make the visual horizon salient Rand et al ( 2012 ) Blur (severe) P–R = 0.46 logMAR = 1.51 (20/647) Distance and size perception of targets on stands Distance: 1.5, 2.7, 4 m Color of stands that the targets were placed on–created high or low contrast with ground plane Blur versus normal vision 1. Distance and size judgments were accurate to the targets presented on the visible black stands 2.…”
Section: Impact Of Low Vision On Space Perception: Use Of Local Featumentioning
confidence: 99%
“…Further support for the importance of ground surface cues for distance in low vision comes from a study that manipulated the visual information for whether an object is in contact with the ground (Rand et al 2012 ). Objects that we interact with often make contact with the ground plane, but that point of ground contact may not always be visible, particularly under blurred viewing conditions.…”
Section: Impact Of Low Vision On Space Perception: Use Of Local Featumentioning
confidence: 99%
See 1 more Smart Citation